Cancer Multidrug Resistance: Safe and Effective Reversal of Cancer Multidrug Resistance Using Sericin‐Coated Mesoporous Silica Nanoparticles for Lysosome‐Targeting Delivery in Mice (Small 9/2017). Issue 9 (March 2017) - Liu, Jia; Li, Qilin; Zhang, Jinxiang; Huang, Lei; Qi, Chao; Xu, Luming; Liu, Xingxin; Wang, Guobin; Wang, Lin; Wang, Zheng
Abstract : Sericin‐wrapped mesoporous silica nanoparticles (SMSNs) with pH and protease dual responsiveness are successfully fabricated as a lysosome‐targeting drug delivery system by Guobin Wang, Lin Wang, Zheng Wang, and co‐workers in article number 1602567. Such a dual responsive system offers a rapid doxorubicin release in lysosomes, which bypasses the membrane pump mediated drug efflux, thereby achieving the reversal of drug resistance.